Transgenerational effects of BDE-209 on male reproduction in F3 offspring rats. (June 2021) - Hsu, Ping-Chi; Li, Zheng-Kuan; Lai, Ching-Shu; Tseng, Li-Ho; Lee, Chia-Wei; Cheng, Fu-Jen; Chang, Chao-Yu; Chen, Jenq-Renn
Abstract: Decabromodiphenyl ether (BDE-209), a congener of polybrominated diphenyl ethers, is a commonly used brominated flame retardant and a known endocrine disrupting chemical (EDC). Knowledge about the effects of prenatal BDE-209 exposure on male reproduction and whether transgenerational effects occur in subsequent generations are scant. Therefore, in this study, we tested the hypothesis that prenatal exposure to BDE-209 disrupted sperm function in the F1, F2, and F3 generations of male rats. Pregnant Sprague-Dawley rats were treated by gavage from gestation day 0 to birth with 5 mg BDE-209/kg/day. This treatment was based on the lowest-observed-adverse-effect level for DNA damage to sperm in male offspring. On postnatal day 84 for all generations, epididymal sperm counts, motility, morphology, reactive oxygen species generation, sperm chromatin DNA structure integrity, testicular DNA content in spermatogenesis, and serum testosterone levels were assessed. DNA methyltransferase (Dnmts) mRNA expression and methyl-CpG binding domain sequencing were also examined to analyze DNA methylation status in the F3 generation. In the F1 generation, prenatal exposure to BDE-209 disrupted body weight, decreased anogenital distance (AGD), sperm count, and motility; and increased bent tail rates of sperm. In the F2 generation, exposure to BDE-209 decreased AGD, sperm count, normal morphology rates, Dnmt1 expression, and increased Dnmt3a expression. In the F3 generation, BDE-209 exposure decreased AGD and normal sperm morphology, disrupted testicular elongated spermatid and round spermatid rates, reduced serum testosterone levels, and inhibited the mRNA expression of Dnmt1 and Dnmt3b. Compared with the control group, there existed 215 differentially hyper-methylated and 83 hypo-methylated genes in the BDE-209 group. BDE-209 is an EDC to disrupt the male reproduction from F1 to F3. BDE-209-induced changes in sperm function and hyper- or hypo-DNA methylation in the F3 generation might therefore explain the possible mechanism underlying BDE-209-mediated epigenetic transgenerational effects on the male reproductive system. Graphical abstract: Image 1 Highlights: BDE-209 exposure reduced AGD and normal sperm morphology rates in the F1–F3. BDE-209 altered testicular cell populations and serum testosterone level in the F3. BDE-209 affected the testicular Dnmt1 and Dnmt3b expression in the F3 generation. BDE-209 changed sperm hyper- and hypo-DNA methylation in the F3 generation. BDE-209-mediated epigenetic transgenerational effects on the male reproduction.